A protocol for a systematic review and meta-analysis of the effect of muscle energy techniques on shoulder joint pain. - Ye Ji Kim; Seojae Jeon; Hyeonjun Woo; Won-Bae Ha; Junghan Lee (PLoS ONE)
Introduction Muscle energy techniques (MET) for shoulder muscles improve both shoulder muscle tension and the range of motion of the glenohumeral joint. This systematic literature review will investigate the effects of MET on shoulder pain as a result of muscle tension in the glenohumeral joints of patients with shoulder disorders and collect clinical evidence regarding the effectiveness of muscle energy techniques on glenohumeral joint pain. Based on previous studies, we anticipate that MET may significantly affect shoulder joint pain. We expect to provide moderate to high levels of evidence regarding the effectiveness of MET in the treatment of shoulder pain. Methods Nine electronic databases will be searched for articles published up to November 2024, including PubMed, EMBASE, CENTRAL, KCI, KISS, KMbase, RISS, DBpia, and OASIS. Search terms will consist of terms related to the outcome (e.g., "shoulder") and intervention (e.g., "muscle energy technique," "post-isometric relaxation," "isometric stretching"). Studies selected for the systematic review and meta-analysis will include randomized controlled clinical trials and studies using MET applied to the human shoulder muscles. Qualitative and case studies will be excluded. Two authors will independently assess each study for eligibility and risk of bias and extract the data. This study will analyze the effects of MET on shoulder pain. Additionally, we intend to demonstrate the effect size of muscle energy techniques on factors such as range of motion. Our study will provide clinical evidence for the effects of muscle energy techniques on shoulder joint pain. Our study aims to provide clinical evidence supporting the moderate-to-high effectiveness of MET in treating shoulder joint pain. Prospero registration ClinicalTrials.gov CRD42024532367.